2015
DOI: 10.1136/annrheumdis-2014-206517
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment with S100A9 inhibitor paquinimod reduces pathology in experimental collagenase-induced osteoarthritis

Abstract: Prophylactic treatment of paquinimod reduces synovial activation, osteophyte formation and cartilage damage in experimental OA with high synovial activation (CIOA) and ameliorates pathological effects of S100A9 in OA synovium ex vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 22 publications
(24 reference statements)
2
58
1
Order By: Relevance
“…Human chondrocytes produce these molecules, and exposure of cartilage explants to S100A8 and S100A9 promoted catabolic (MMP-1, MMP-3, MMP-13, IL-6, IL-1β) and suppressed anabolic gene expression (aggrecan and Collagen type II) in a TLR-4 dependent manner [104]. Moreover, S100A9 deficient mice exhibited reduced disease in the collagenase model, but not the DMM model of OA, [104, 105] and disease was inhibited by pharmacologically reducing S100A9 expression [106]. The differential effects in these two models were attributed to more robust synovial activation in the collagenase model, which is induced by intra-articular injection of bacterial collagenase leading to instability of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Human chondrocytes produce these molecules, and exposure of cartilage explants to S100A8 and S100A9 promoted catabolic (MMP-1, MMP-3, MMP-13, IL-6, IL-1β) and suppressed anabolic gene expression (aggrecan and Collagen type II) in a TLR-4 dependent manner [104]. Moreover, S100A9 deficient mice exhibited reduced disease in the collagenase model, but not the DMM model of OA, [104, 105] and disease was inhibited by pharmacologically reducing S100A9 expression [106]. The differential effects in these two models were attributed to more robust synovial activation in the collagenase model, which is induced by intra-articular injection of bacterial collagenase leading to instability of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, S100A8/A9 was shown not only to activate the catabolic aspects of OA, but additionally promotes the anabolic process of ectopic bone/osteophytes formation, both in the CiOA experimental model and in early human OA, possibly via MMP-mediated remodelling of the cartilage matrix that allows osteophytes to increase in size [133]. This is underlined by the finding that S100A8/A9 induces Wnt signalling, which has been shown to promote bone formation [134].…”
Section: S100 Proteinsmentioning
confidence: 99%
“…Lees et al [27■■] showed that a 32-mer peptide of aggrecan, generated by sequential enzymatic cleavage in joints of patients with osteoarthritis, promotes catabolism and suppresses anabolic gene expression via MyD88 and TLR-2 in murine and human chondrocytes, synovial fibroblasts, and macrophages. Another group provided evidence that pharmacologic interference with alarmins may provide therapeutic opportunities [28■■]. The S100A8 and S100A9 proteins can drive cartilage inflammatory activity and catabolic responses via TLR-4, as well as disease progression in the collagenase murine model of osteoarthritis.…”
Section: Damage Associated Molecular Patterns and Alarminsmentioning
confidence: 99%
“…The S100A8 and S100A9 proteins can drive cartilage inflammatory activity and catabolic responses via TLR-4, as well as disease progression in the collagenase murine model of osteoarthritis. These investigators have now used paquinimod, which prevents S100A9/TLR binding, to block synovial inflammatory activity in vitro and ameliorate joint damage in the same model [28■■]. Interference with PRRs and their ligands has not yet been translated to human disease, but these studies provide promise for future developments.…”
Section: Damage Associated Molecular Patterns and Alarminsmentioning
confidence: 99%